Using a Narrative Tool to Help Quebec English-Speaking Students Produce Personal Histories of Belonging (LEARNing Landscapes, 2018)
This article introduces Jörn Rüsen’s concept of narrative competence as a useful pedagogical framework for operationalizing a remedial narrative tool designed to help make room for Quebec’s English-speaking minority in the teaching of school history. Developed through empirical research and representing a schema-like narrative structure, the Narrative Template Tool’s aim is to assist students to produce and validate personal (his)stories of belonging through conducting original historical research. To counter the dangers of indoctrination, the tool moreover employs a feature of the orientation component of narrative competence—use-of-history—as a means of helping students account for their emerging perspectives.
Keywords: narrative competence; narrative tool; historical consciousness; history teaching; minority exclusion; English-speaking Quebec; community